2017
DOI: 10.1007/s00221-017-5005-5
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary reduction of force variability via modulation of low-frequency oscillations

Abstract: Visual feedback can influence the force output by changing the power in frequencies below 1 Hz. However, it remains unknown whether visual guidance can help an individual reduce force variability voluntarily. The purpose of this study, therefore, was to determine whether an individual can voluntarily reduce force variability during constant contractions with visual guidance, and whether this reduction is associated with a decrease in the power of low-frequency oscillations (0-1 Hz) in force and muscle activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Even though the task was not cognitively challenging, it did require a certain level of attention. Therefore, age-associated decreases in the high-frequency components of the neural drive to muscle may have reflected an impairment in the cortical control that contributed to the augmented fluctuations of common input at lower frequencies (Kwon et al 2012;Lodha and Christou 2017;Park et al 2017). Because of the weak association between gamma coherence and age and the relatively small sample size in our study, however, this interpretation should be further tested in future studies.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Even though the task was not cognitively challenging, it did require a certain level of attention. Therefore, age-associated decreases in the high-frequency components of the neural drive to muscle may have reflected an impairment in the cortical control that contributed to the augmented fluctuations of common input at lower frequencies (Kwon et al 2012;Lodha and Christou 2017;Park et al 2017). Because of the weak association between gamma coherence and age and the relatively small sample size in our study, however, this interpretation should be further tested in future studies.…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, assuming an approximately linear transmission of common input by the pool of motor neurons (Negro and Farina 2011), the neural drive to muscle produces a force that reflects the low-frequency components of the common synaptic input (Farina et al 2014(Farina et al , 2016. Accordingly, previous studies have suggested that lowfrequency oscillations in force (Ͻ0.5 Hz) during voluntary contractions can be modulated by increasing the frequency of oscillation with visual feedback and motor training (Fox et al 2013;Lodha and Christou 2017;Moon et al 2014;Park et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The window size was 15 s providing a resolution of 0.06 Hz. The dependent variable was the proportion of power in the 0-0.25 Hz and 0.25-0.5 Hz relative to the total power of the force signal from 0 to 2 Hz [Moon et al, 2014;Park et al, 2017Park et al, , 2019. Power was made relative to 2 Hz since approximately 95% of total power of the static force signal is located between 0 and 2 Hz.…”
Section: Power Spectrum Analysismentioning
confidence: 99%
“…Power spectral density (PSD) analysis was performed using the Welch algorithm according to procedures outlined in from previous studies [Lodha et al, 2013; Moon et al, 2014; Park, Casamento‐Moran, Yacoubi, & Christou, 2017]. The static force signals were down sampled from 2000 Hz to 1000 Hz and detrended to remove bias from the signal.…”
Section: Signal Processing and Data Reductionmentioning
confidence: 99%
“…For instance, significant correlations between F CoV and CoV for motor unit discharge rate were found in younger individuals [ 7 ]. Collectively, low-frequency oscillations in force may be consequences of variability in a single motor unit’s firing rate or low-frequency oscillations in the neural drive to the muscle, commonly estimated by the cumulative spike trains or the rectified-and-smoothed EMG (rsEMG) [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%